2D MoO2/N-Doped-carbon nanosheets as SERS tweezers: a non-noble metal reusable substrate for selective organic dye detection - Gaikwad, Supriya Hanmant; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2021)
The design and synthesis of a highly sensitive and exceptionally selective surface-enhanced Raman scattering (SERS) substrate with an excellent reusable property are of significant interest because of its vast prospective application in actual and complicated detection environments. Here, a simple synthesis strategy was presented to fabricate crystalline two-dimensional (2D) MoO2/N-doped-carbon nanosheets with the plasmonic property. The morphology, crystal phase, and surface property of MoO2 nanomaterials (NMs) were specifically controlled under suitable reaction conditions. In addition, the plasmonic MoO2/N-doped-carbon NM exhibited a SERS maximum enhancement factor up to 1.38 × 104 with a detection limit as low as 1.0 × 10–6 M. More importantly, the as-synthesized nanocomposite shows high selectivity as a “SERS Tweezer” toward methylene blue (MB) in binary and ternary mixed interfering analyte solutions, preserving detection sensitivity toward MB for three cycles via an “elect-and-eliminate” approach. This strategy will be helpful to design other plasmonic semiconductor NMs for successful tangible applications of selective SERS sensing for trace impurity detections in real and complex environments.